Effectiveness of alternative GSM therapies: "twist of fate" or natural evolution? - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov (Гинекология, 2022)
The study and development of new therapies for genitourinary syndrome of menopause (GSM) remain an area of focus in modern gynecology. The relevance and need for scientific research in this area are undeniable due to the significant negative impact of GSM on patients' quality of life. At this point, however, a great deal of controversy is arising as the knowledge of the treatment of GSM-associated disorders deepens. Local hormonal therapy remains the "gold standard" for vulvovaginal atrophy treatment, but alternative therapies for GSM are launching in the pharmaceutical market. Have we got more answers? Yes. Have we got more questions? Sure. So why does the very fact of studying GMS require us to be so pedantic and focus the attention of the entire global medical community? Let's get to the bottom of this.